Cut-off point of abdominal perimeter adjusted to body mass index for overweight and obesity in the peruvian population - Guevara Tirado, Alberto (2024)
Objective: To establish the cut-off point of the abdominal perimeter for overweight and obesity adjusted to the body mass index in adults of the Peruvian population. Material and methods: Observational, analytical, retrospective and cross-sectional study based on data from the national demographic and family health survey (ENDES). There was no sample calculation because the entire population was analyzed. The variables were: sex, abdominal perimeter and body mass index (BMI). Results: With an area under the curve of 0.954 in women and 0.952 for men, an abdominal perimeter of 86 centimeters was established as the cut-off point for overweight in women, with a sensitivity (S) of 90%, and a specificity (E) 89% and for obesity an abdominal perimeter of 95 centimeters (S=89%, E=85%). In men, an abdominal perimeter of 89 centimeters (S=87%, E=87%) was established as a cut-off point to determine overweight and an abdominal perimeter of 99 centimeters (S=88%, E=90%) for obesity. Based on the new cut-off points, a higher prevalence of overweight and obesity was found in women (69% and 29%) than in men (60% and 19%), with a better association, agreement and confidence interval of the Odds. Ratio with respect to the analysis of abdominal perimeter and BMI prior to the COR analysis. Conclusions: The abdominal perimeter cut-off points adjusted to BMI in men were 89 centimeters for overweight and 99 centimeters for obesity, and in women it was 86 centimeters for overweight and 95 centimeters for obesity.